2015
DOI: 10.1080/10406638.2014.964424
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dissipation, Adsorption, Degradation, and Leaching of Triazophos Pesticide in Various Soils

Abstract: This study concerns the investigation of dissipation, adsorption, and degradation of triazophos in different soils from Pakistan. These processes help in the disappearance of pesticide from the environment. Gas chromatography was used for dissipation and adsorption analysis while for degradation study mass spectrometer was used in addition of gas chromatography (GC-MS). The dissipation rate of triazophos in three different soils was 90% over 30 days with average half-life of 9.059 days. From dissipation study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…These results are in accordance with Jiang et al (2010) who reported 3.75 days half-life of profenofos in paddy soil. Results obtained by Bajeer et al (2016) showed little deviation from present studies as they reported 9.1 days half-life of triazophos in various types of soils.…”
Section: Dissipation Of Profenofos and Triazophos From Okra Cropped Soilcontrasting
confidence: 64%
“…These results are in accordance with Jiang et al (2010) who reported 3.75 days half-life of profenofos in paddy soil. Results obtained by Bajeer et al (2016) showed little deviation from present studies as they reported 9.1 days half-life of triazophos in various types of soils.…”
Section: Dissipation Of Profenofos and Triazophos From Okra Cropped Soilcontrasting
confidence: 64%
“…The functional groups (carboxyl, hydroxyl, amino, etc.) of soil organic matter and clay particles were not conducive to the mobility of pesticides [26]. Furthermore, the mobility of pesticides in soil was also related to their solubility, the pesticides with good solubility were not easily adsorbed but easily leached [27][28][29].…”
Section: Discussionmentioning
confidence: 99%